Modal Sosial Caleg Pendatang Baru dalam Pileg Kabupaten Bangli Tahun 2019 - Dika Nugraha, Sang Putu; Pramana, Gede Indra; Apriani, Kadek Dwita (Jurnal Nawala Politika, 2023)
This study aims to determine the form and utilization of social capital possessed by newcomer legislative candidates, namely I Gusti Nyoman Bagus Triyana Putra, in the 2019 general election so that he gets a large number of votes by using the social capital theory from David Putnam. Based on the findings of the data obtained, it can be concluded that social capital which includes networks, beliefs, and norms is indeed owned by Triyana Putra and plays a very important role so that it gets great support from the community, with the involvement of community leaders who make sabha desa to fully support Triyana Putra as a candidate for legislative representative from the Bebalang Traditional Village. In addition, there is a big influence from Triyana Putra's closeness to the political elite and also the full support of his party, the Partai Demokrasi Indonesia Perjuangan. So that Triyana Putra was elected with the highest vote acquisition in Constituency 1 Bangli with 5,292 votes.